"It's a Student Strike but a People's Struggle": Class in the 2012 Québec's "Maple Spring". Issue 3 (26th August 2016) - Bonin, Hugo
Abstract : In 2012, the province of Quebec witnessed the largest and longest student strike in North America of the last fifty years. The objective of this article is twofold: first, present an account of the events as they unraveled, by relying on both first and second‐hand sources, in order to lay the ground for future comparative studies. Second, on a more theoretical level, to assess the class character of the 2012 movement, using the concepts of class relations and class recomposition. While the Printemps Érable might not be at first sight a "classed‐based movement, " a study of more recent mobilizations in Québec helps to shed light on its effect on class relations. By doing so, I hope to engage the conversation on the question of class in contemporary social movements.